Assessment of Antibiotic Management for Catheter-Associated Urinary Tract Infection: An Observational Study at a Tertiary Care Hospital, Bangalore - Banerjee, Sudeshna; Ramaiah, Balakeshwa (Indian Journal of Pharmacy Practice)
Background: Catheter-Associated Urinary Tract Infection (CAUTI) is a common healthcare-associated infection that contributes significantly to patient morbidity, prolonged hospital stays and increased healthcare costs. This study aims to evaluate the antibiotics used in CAUTI treatment and identify the pathogens responsible, contributing to improved management and patient outcomes. Materials and Methods: A prospective observational study spanning six months was performed at a tertiary care institution. Data were collected from 60 patients diagnosed with CAUTI. The study examined patient demographics, antibiotic regimens, pathogen identification and antibiotic sensitivity profiles. Outcomes were assessed based on clinical improvement and microbiological results. Results: Among the 60 patients, 42% were treated with Inj. Cefoperazone and sulbactam. Escherichia coli emerged as the most frequent pathogen, identified in 57% of cases, with Klebsiella species following at 17%. Antibiotic therapy was adjusted in 42% of cases based on culture sensitivity results. The most commonly used catheters were Foley’s catheters, accounting for 77% of the cases. Conclusion: This study emphasizes the significance of using targeted antibiotic therapy, guided by culture sensitivity results, in managing CAUTI. The findings underline the need for stringent infection control measures and the importance of adhering to antibiotic stewardship programs to reduce CAUTI incidence and improve patient outcomes.
Keywords: Catheter-associated urinary tract infection; Antibiotics; Escherichia coli; Hospital acquired infection; Antibiotic Resistance